Social Media influences on Purchase Intention among Youth in Malaysia - Ngo Pei Shi; Siti Norziah Ismail (Research in Management of Technology and Business, 2021)
The social media become important in everybody’s life and social media as a tool to explore the world just by clicking on the phone or computer. Nowadays, many companies use the social media platform to promote and sell their products and services to the consumers. The consumers also accept and like to purchase the products and services through social media especially the youth because they access the social media platform regularly. However, there is some problems that faced by the consumers when they are using the social media platforms to purchase the products and services. Therefore, the purpose of this research is to determine the factors affecting the use of social media influences on purchase intention among youth in Melaka and determine the most influential factor affecting the purchase intention among youth in Melaka on the social media platforms. In this research, the researcher uses quantitative method and non-probability sampling method. A total of 262 sets of questionnaires are collected from the youth in Melaka through online. The respondents answer according to the 5-points Likert scale and researcher analyzed the data through Statistical Package for the Social Sciences (SPSS) version 20 software. The findings showed that there is positively significant relationship between brand credibility, celebrity endorsement, subjective norm, and trust toward purchase intention. Moreover, subjective norm is the most influential factor that influence youth purchase intention on social media platform. Therefore, future researcher can investigate the relationship between the other variables in social media platform and expand the population area.